The Influence of Self-Efficacy, Emotional Intelligence and Learning Motivation on Learning Achievement of Students at Universitas Jambi - Robi Hendra; Bradley Setiyadi; Affriliani; Yusa Hendra Pratama; Denny Denmar; Hansein Arif Wijaya; Jehlie Alaisa Marasigan Contreras (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2024)
This research aimed to analyze the influence of self-efficacy, emotional intelligence, and learning motivation on the academic performance of students in the Faculty of Education and Teacher Training (FKIP) at the Universitas Jambi. The study utilized a quantitative approach and the data collection technique involved distributing and collecting questionnaires (surveys) through Google Forms. The respondents selected for this study were students from FKIP at the Universitas Jambi, with a sample size of 218 respondent from total population of 8,968. The data analysis technique used Partial Least Squares-Structural Equation Modeling (PLS-SEM) to develop a model that describes the relationships between the variables. The results of indicated that, in the first hypothesis, self-efficacy has a P-value of 0.007, indicating a significant influence on academic performance. In the second hypothesis, emotional intelligence has a P-value of 0.008, also showing a significant influence on academic performance. Finally, in the third hypothesis, learning motivation has a P-value of 0.008, suggesting a significant influence on academic performance. Therefore, this research concluded that self-efficacy, emotional intelligence, and learning motivation have a positive and significant impact on students' academic performance. Based on these findings, this research contributed to the understanding that increasing self-efficacy, emotional intelligence, and learning motivation can significantly improve students' academic achievement. Therefore, interventions designed to improve these aspects can be an effective strategy for improving academic performance among students at the Faculty of Education and Teacher Training, Universitas Jambi.